Aplikasi Menara Masjid dan Pengumpulan Zakat pada BAZNAS Kota Palembang: Kajian Hukum Ekonomi Syariah - Dea Widya Feranita; Legawan Isa (Journal of Sharia and Legal Science, 2026)
Digitalization of zakat management is one of the efforts to increase the effectiveness, efficiency, transparency, and accountability of zakat fund collection. One of the innovations developed by the National Zakat Agency (BAZNAS) is the Menara Masjid Application as a digital-based zakat collection medium. This study aims to analyze the mechanism of using the Menara Masjid Application in zakat fund collection at BAZNAS Palembang City and review it from the perspective of Sharia Economic Law. This study uses an empirical juridical method with a qualitative approach. Data were obtained through observation, interviews, documentation, and literature studies, then analyzed descriptively qualitatively. The results show that the Menara Masjid Application makes it easier for the community to pay zakat and supports more systematic, transparent, and accountable recording. However, its implementation is not optimal due to still being hampered by low digital literacy of the community, limited manager competence, unequal use of the application, and network and system disruptions. From the perspective of Sharia Economic Law, the use of the Menara Masjid Application is in accordance with the principles of justice, trust, maslahah, transparency, and accountability because it provides convenience without conflicting with sharia provisions. This research contributes as a basis for strengthening digital zakat governance that is more effective and in accordance with the principles of Islamic Economic Law.